Processos educativos emergentes da formação de Mediadores(as) do Fútbol Callejero: percepção dos(as) formadores(as) - Varotto, Nathan Raphael (2024)
Football is a global phenomenon that is present in the lives of many people, be it for their favorite team, a match with friends on the street field, a high school game, in championships, newspapers and in academic research, so it can be say that football also acts in education and in light of this it provoked and still provokes a lot of dialogue about this phenomenon and allows interpretations, understandings, different appropriations, debates, starting by pluralizing football, hence in this thesis we draw attention to football, focusing on the manifestation called Fútbol Callejero, more specifically the mediators formation of Fútbol Callejero. This game was initially structured and experienced in Moreno, on the outskirts of the metropolitan area of Buenos Aires, Argentina, based on a proposition by former professional football player Fabián Ferraro, aiming to reduce violence in the aforementioned neighborhood and its surroundings, as well as integration, autonomy and proactivity of young people. That said, we present the research question: What educational processes emerge from the mediators formation of Fútbol Callejero from the trainers’ perspective? The central objective of this study is: to analyze, understand and describe the educational processes emerging from the mediators formation of Fútbol Callejero from the trainers' perspective. The methodological trajectory is based on phenomenology, a situated phenomenon modality. For data collection, interviews were used with the trainers of Fútbol Callejero, as they enable the literal transcription of the speeches given, which allows the uninterpreted description (genuine speech) of the subjects' experiences. Data analysis was also based on phenomenology, based on the situated phenomenon and from an initial analysis, two categories emerged, namely: A) “Forming transforming” and B) “Seeing the young people, one day, in our place, giving this formations.” We consider the commitment of the trainers not to carry out training with a technicalist bias but rather a reflexive and dialogical one, respecting the proposition of structuring Fútbol Callejero in the epistemological South, in Moreno, on the outskirts of Buenos Aires, Argentina. Thus, they think about and promote the formation process, observing the origin of the mediators, the appreciation of the group's knowledge and doing-with.